Intercollegiate Athletics Marketing-Generated Revenue: Within Autonomy Football Bowl Subdivision - Alicia Romano; Jamie Riggs; Alan Morse; Yoon Tae Sung (Journal of Applied Sports Management, 2021)
Intercollegiate athletic market-generating revenue (MGR) is of interest to administrators for increasing institution revenue. The driving factors of MGR (i.e., conference, facilities, and finances) need to be understood to allow target level planning for increasing MGR. Multiple linear regression was used to assess MGR on a sample of U.S. autonomy Football Bowl Subdivision institutions. Per capita attendance by designated marketing area, capacity, and contributions were shown to have a strong, quantifiable influence on MGR. By setting the levels of the facility and financial determinant variables, and adjusting for conference, the MGR may be predicted or targeted for institution revenue goals.
Keywords: marketing-generated revenue; intercollegiate athletics; autonomy football bowl subdivision